Explorating Potencial Investment in Pangkalpinang - Reniati Reniati; Zikri Rahmani; Nurwasya Nurwasya; Ria Atlantika (Universitas Bangka Belitung, 2024)
Pangkalpinang city has abundant natural resource potential and has promising investment potential for investors. The Pangkalpinang city government supports investment through policies that are pro-business and ease of doing business. With the potential for abundant natural resources such as tin, as well as the marine, fisheries and tourism industries, it is hoped that they will be able to support the sustainable economic growth of Pangkalpinang city. This research aims to determine the leading sectors that have investment potential in Pangkalpinang city. This research was conducted in the city of Pangkalpinang. The data source in this research uses secondary data in the form of a time series from the Gross Regional Domestic Product (GRDP) of Pangkalpinang city for 2018-2022. The analytical tools used in this research are: 1). Location Quotient (LQ) analysis is used to determine the base and non-base sectors in the economy of Pangkalpinang city 2). Shift Share analysis is used to determine changes and shifts in the economic structure of Pangkalpinang city. The results of this research show that there are 4 non-based sectors and 13 basic sectors based on LQ analysis and based on shift share analysis, there are 11 industries that have excellent location advantages or grow faster than the same industry elsewhere. This makes the city of Pangkalpinang a city worthy of being an investment destination.